2020
DOI: 10.1155/2020/4253026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Both Soil Properties and Geometric Parameters on Failure Mechanisms and Stability of Two‐Layer Undrained Slopes

Abstract: The stability of the two-layer undrained clay slopes should be given considerable attention since they are commonly observed in nature and in manmade structures, and they traditionally have low stability. Therefore, with the elastoplastic finite element method, this paper thoroughly explores the influence of the soil strength parameter cu, slope angle β, and slope depth ratio DH on the slope stability and failure mechanisms by the wide-ranging parametric changes. The aims of this study are also to find the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Traditional stabilizers include slag (Wild et al, 1998;Gao et al, 2021), coal furnace fly ash (Kolias et al, 2005;Show et al, 2003;Arulrajah et al, 2018;Disfani et al, 2015), cement and lime (Lemaire et al, 2013), cement cellar dust (Baghdadi et al, 1997;Miller and Azad, 2000;Rivard-Lentz et al, 1997), domestic waste incineration slag (Kukko, 2000;Consoli et al, 2019), unconventional additives (Seco et al, 2011;Urena et al, 2013), lignin (Cai et al, 2016), alkaline activators (Cristelo, et al, 2012;Wang, et al, 2019), lime (Little, 1995;Choobbasti, et al, 2010), and calcium carbide residue (Jiang, et al, 2016;Du, et al, 2016). To date, silt stabilization research and practice have made good progress (Indraratna et al, 2012;Kavitha et al, 2015), but there is still much room for improvement, including stabilization effectiveness and cost (Marto et al, 2014;Suksiripattanapong, et al, 2015;Guo et al, 2020b;Wang, et al, 2021b).Based on a new slope protection system of three composite layers [silt and polyacrylamide (SP layer); silt, basalt fibre and polyacrylamide (SBP layer); and silt and basalt fibre (SB layer)], the aim of this study is to explore the anti-infiltration and anti-erosion performances of the composite layers and discuss the thicknesses of the SP, SBP and SB layers by means of mechanical and erosional experiments and the rainfall infiltration and erosion of numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional stabilizers include slag (Wild et al, 1998;Gao et al, 2021), coal furnace fly ash (Kolias et al, 2005;Show et al, 2003;Arulrajah et al, 2018;Disfani et al, 2015), cement and lime (Lemaire et al, 2013), cement cellar dust (Baghdadi et al, 1997;Miller and Azad, 2000;Rivard-Lentz et al, 1997), domestic waste incineration slag (Kukko, 2000;Consoli et al, 2019), unconventional additives (Seco et al, 2011;Urena et al, 2013), lignin (Cai et al, 2016), alkaline activators (Cristelo, et al, 2012;Wang, et al, 2019), lime (Little, 1995;Choobbasti, et al, 2010), and calcium carbide residue (Jiang, et al, 2016;Du, et al, 2016). To date, silt stabilization research and practice have made good progress (Indraratna et al, 2012;Kavitha et al, 2015), but there is still much room for improvement, including stabilization effectiveness and cost (Marto et al, 2014;Suksiripattanapong, et al, 2015;Guo et al, 2020b;Wang, et al, 2021b).Based on a new slope protection system of three composite layers [silt and polyacrylamide (SP layer); silt, basalt fibre and polyacrylamide (SBP layer); and silt and basalt fibre (SB layer)], the aim of this study is to explore the anti-infiltration and anti-erosion performances of the composite layers and discuss the thicknesses of the SP, SBP and SB layers by means of mechanical and erosional experiments and the rainfall infiltration and erosion of numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The design parameters (e.g., heap height, slope gradient) and construction parameters (e.g., layer thickness, heap speed) significantly affect the slope stability of a soft soil dump (Zhang, 2019;Li, 2020). Many researchers found that higher heap height and/or steeper slope gradient resulted in lower safety factor of soft soil slopes (Kjaernsli and Simons, 1962;Lim et al, 2015;Zhang, 2019;Guo et al, 2020). By using the response surface method and the finite element-based software (Plaxis 2D), respectively, Kostić et al (2016) and Shiferaw (2021) found the stability of clay slopes improved with decreasing heap height and/or slope gradient.…”
Section: Introductionmentioning
confidence: 99%
“…However, both the analysis of dynamic propagation (Chen et al, 2006;Baggio et al, 2021; and the assessment of the rockfall movement distance (Chen et al, 2010;Zhu et al, 2020;Donati et al, 2021;Ma et al, 2021) were closely related to the influence of initiating damage factors on the triggering mechanism in rockfalls. There are Some other studies on earthquake-induced rock avalanches focus on other damage modes, such as spatial slip mode, compression shear-slip mode, tensile-tipping mode, and rarely on earthquake-induced sequential collapse damage mode (Togo et al, 2014;Zeng et al, 2019;Guo et al, 2020b;Guo et al, 2020c;Do et al, 2020;Yang et al, 2022). Sequential collapse is an initial damage situation of earthquake-induced rock avalanche, which often occurs on weathered and fractured rock cliffs near the horizontal strata, where the triggering mechanism is different from the isolated rock fall mode caused by differential weathering or improper excavation (Singeisen et al, 2020;Aaron et al, 2016;Aaron et al, 2019;Dufresne et al, 2016;Hilger et al, 2019).…”
mentioning
confidence: 99%